FORMATION OF LEADERSHIP QUALITIES AMONG STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS (Scientific journal of the Fergana State University, 2023)
In this article, the role of motivation and motivation in the formation of students' social activity skills, as well as the importance of their practical application, is investigated on a scientific basis. The quality of education in the developed countries of the world. About the development of five different initiatives aimed at attracting young people to culture, theater, art, wide involvement in physical education and sports, the use of computer technology and the Internet, the popularization of reading, the involvement of girls in socially active life. About the development of "road maps" for the strategic development of higher education institutions, joint faculties and branches of universities have been created in cooperation with leading universities of foreign countries.